Thromboembolism and Anticoagulation in Pancreatic Cancer - Habib, Muzzamal; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
Pancreatic cancer is a hypercoagulable condition, and venous thromboembolism affects up to 17% to 57% of pancreatic cancer patients. Initiating chemotherapy further increases the risk. For cancer patients initiating chemotherapy, there is currently no approved treatment for the primary prevention of venous thromboembolism risk. The authors summarize the two abstracts (#151 and #284) presented at the 2013 ASCO Gastrointestinal Cancers Symposium which were focused newer treatment options and the incidence of thromboembolism in pancreatic cancer patients especially in East Asian patients. Additionally the authors review the risk of thrombosis associated with the chemotherapy and erythropoiesis stimulating agents and its prognostic implications and possible managements. Image: St. Elizabeth’s Medical Center. Brighton, MA, USA.